Performance simulation of Single Carrier Frequency Division Multiple Access modulation of uplink LTE system - I. Elkafrawi (Journal of Pure & Applied Sciences, 2019)
Since past few decades different types of cellular networks were launched and went successful on the radio links such as WiMAX, that became very popular because of its high data rate (70Mbps) and support for providing wireless internet services over 50km distance. The UMTS Long Term Evolution (LTE) is an emerging technology in the evolution of 3G cellular services. LTE runs on an evolution of the existing UMTS infrastructure already used by over 80 percent of mobile subscribers globally. We have very limited resources in cellular technologies and it is important to utilize them with high efficiency. Single Carrier Frequency Division Multiple Access (SC-FDMA) is introduced recently and it became handy candidate for uplink multiple access scheme in LTE system that is a project of Third Generation Partnership Project (3GPP). In this paper, we investigate the performance of SC-FDMA of LTE system by considering different modulation schemes (BPSK, QPSK, 16QAM and 64QAM) on the basis of peak to average power ratio( PAPR), bit error rate (BER), power spectral density (PSD) by simulating the model of SC-FDMA. We use Additive White Gaussian Noise (AWGN) channel and introduce frequency selective (multipath) fading in the channel by using Rayleigh Fading model to evaluate the performance in presence of noise and fading.